The manipulated photographic images of Man Ray and Moholy-Nagy: "a deconstructural approach" - Fry, Roger Bruce (Rhodes University, Faculty of Humanities, Department of Fine Art, 1986)
From introduction: In the following essay an emphasis has been placed on manipulated photographic images. Although this implies a whole variety of ways in which these images can be manipulated e.g. in collage, silkscreen etc., the emphasis here is on images that have a fabricated or deliberate manipulation of subject matter to make up the photograph.
Keywords: Man Ray, 1890-1976; Moholy-Nagy, László, 1895-1946; Photography, Artistic